Cultures of Witchcraft in Europe from the Middle Ages to the Present (Palgrave Historical Studies in Witchcraft and Magic, 2018)
This volume is a collection based on the contributions to witchcraft studies of Willem de Blécourt, to whom it is dedicated, and who provides the opening chapter, setting out a methodological and conceptual agenda for the study of cultures of witchcraft (broadly defined) in Europe since the Middle Ages. It includes contributions from historians, anthropologists, literary scholars and folklorists who have collaborated closely with De Blécourt. Essays pick up some or all of the themes and approaches he pioneered, and apply them to cases which range in time and space across all the main regions of Europe since the thirteenth century until the present day. While some draw heavily on texts, others on archival sources, and others on field research, they all share a commitment to reconstructing the meaning and lived experience of witchcraft (and its related phenomena) to Europeans at all levels, respecting the many varieties and ambiguities in such meanings and experiences and resisting attempts to reduce them to master narratives or simple causal models. The chapter 'News from the Invisible World: The Publishing History of Tales of the Supernatural c.1660-1832' is available open access under a CC BY 4.0 license at link.springer.com.